De historie van de vesting Naarden - Vrankrijker, A. C. J. (Bussum van Dishoeck, 1965)
Description of the history of the Naarden fortress. Both the Eighty Years' War and later wars are discussed. Prussians (patriotic era) and French are covered as well as preparations for WWI.
Keywords: 20th Century (1901-2000); History; Naarden (Netherlands)